1995
DOI: 10.1159/000119227
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Perfusion, Electrical Activity and Effects of Serotonergic Treatment in Obsessive-Compulsive Disorder

Abstract: An abnormally increased glucose metabolism has been described with positron emission tomography (PET) in frontal and caudate regions of obsessive-compulsive patients. Perfusion and electroencephalographic studies have been less conclusive. However, these techniques are, currently, more available than PET and, therefore, deserve further study because of their possible clinical applications. In this article, 13 obsessive-compulsive patients were studied with quantitative EEG and auditory and visual evoked potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 24 publications
2
7
0
1
Order By: Relevance
“…extremely cautious and responsible attitude of the former vs. disinhibited attitude of the latter). Moreover, a hyperactivity of executive control would be consistent with the hyperactivity of the fronto‐striato‐thalamic pathway reported by the majority of brain imaging studies (8, 30–35, 42–45).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…extremely cautious and responsible attitude of the former vs. disinhibited attitude of the latter). Moreover, a hyperactivity of executive control would be consistent with the hyperactivity of the fronto‐striato‐thalamic pathway reported by the majority of brain imaging studies (8, 30–35, 42–45).…”
Section: Discussionsupporting
confidence: 86%
“…According to Carlsson (41) a cortical hyperactivation in the fronto‐striato‐thalamic circuits could be the mechanism underlying this strategy. This hypothesis is in line with the findings of hyperactivity of the fronto‐subcortical pathways reported by brain imaging investigations (8, 29–33, 42–45) and of a relationship between the slow alpha reduction (suggesting a hyperactivity of the functional circuits involved in the selective attention processes) and the time to perform the Self‐Ordered Pointing Tasks for drawings (SOPT‐D) (46).…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Several studies reported increased metabolism and hyperactivity in several areas in OCD patients, including the BG (Swedo et al, 1989; Baxter et al, 1992; Molina et al, 1995; Perani et al, 1995), OFC (Baxter et al, 1988; Molina et al, 1995; Alptekin et al, 2001), and ACC (Swedo et al, 1989; Molina et al, 1995; Perani et al, 1995) cortices (see Figure 1). Furthermore, there is evidence of decreased activation in the DLPFC and parietal cortex during symptom provocation (Maltby et al, 2005; Van Den Heuvel et al, 2005; Viard et al, 2005; Remijnse et al, 2006).…”
Section: Neuroimaging Findings In Ocd: the Role Of The Ofc Acc And Bgmentioning
confidence: 99%
“…Im Großen und Ganzen unterstützen die Befunde aus funktionellen Ruhestudien, in denen Patienten mit Kontrollgruppen verglichen wurden, das Konzept der Dysfunktion der kortiko-striato-thalamo-kortikalen Schleife. Es liegen mehrere Studien mit FDG-PET (4-6, 42) und SPECT (37,58,59) Eine für die Diagnose Zwangsstörung relativ spezifische Beobachtung stellen Leistungsdefizite bei der Durchführung von Arbeitsgedächtnisaufgaben dar (47). Diese äußern sich in schlechterer Erinnerungsleistung und niedrigerer Verarbeitungsgeschwindigkeit (Reaktionszeit) im Vergleich zu Gesunden, aber auch zu Patienten mit Depression und Angststörungen (47).…”
Section: Ruhemetabolismus Und Zerebraler Blutflussunclassified